Earnings Informativeness in Emerging Markets: The Role of Income Smoothing, Foreign Ownership, and Information Asymmetry - Ira Febrianti; Johannes Simatupang; Enggar Diah Puspa Arum; Tona Aurora Lubis (Greenation International Journal of Economics and Accounting, 2026)
This study examines the effect of income smoothing and foreign ownership on earnings informativeness with information asymmetry as a moderating variable in emerging markets. Earnings informativeness reflects the ability of accounting earnings to provide relevant information for investors in predicting future corporate performance. This study employs a quantitative approach using panel data from 55 companies listed on the Indonesia Stock Exchange during the 2020–2022 period, resulting in 165 firm-year observations. Earnings informativeness is measured using the Future Earnings Response Coefficient (FERC), while information asymmetry is measured using the bid-ask spread. Data analysis is conducted using panel data regression with the Random Effect Model (REM). The results show that foreign ownership has a significant negative effect on earnings informativeness, whereas income smoothing has no significant effect. In addition, information asymmetry does not moderate the relationship between income smoothing, foreign ownership, and earnings informativeness. However, information asymmetry has a significant direct effect on earnings informativeness, indicating that the information environment plays an important role in how investors interpret financial information in emerging markets. The findings also suggest that FERC remains a useful forward-looking measure for examining earnings informativeness in emerging markets, particularly during periods characterized by economic uncertainty and information asymmetry.